Kontribusi Gaya Kepemimpinan Dan Sistem Upah Terhadap Kinerja Karyawan Pada Sentra Industri Gitar Desa Rombo, Kecamatan Baki, Kabupaten Sukoharjo Tahun 2015 - Mayasari, Retno Lia; , Dra. Titik Asmawati,SE.,M.Si (2016)
The purpose of this study to determine the contribution: 1) leadership style on employee performance; 2) the system of wages on employee performance; 3) leadership style and system of wages on employee performance. This type of research is descriptive quantitative research. The study population was all employees in industrial centers guitar Ngrombo Village, District Baki, Sukoharjo regency totaling 111 employees with 84 samples taken by proportional random sampling technique. Data was collected by questionnaire. The questionnaire tested the validity and reliability test requirements and conducted data analysis technique used is multiple linear regression analysis, t-test, F, ui R2 and the relative contribution and effective. The results using regression analysis regression equation: Y = 1.136 + 0,291X1 + 0,770X2. The research found that: 1) there is a significant positive contribution and leadership style on employee performance is evidenced by 0.291 regression coefficient is positive and obtained t <t table is 2,042> 1,990dan significance value <0.05 is 0,044; 2) there is a significant and positive contribution to the performance of the employee wage system is evidenced by the regression coefficient of 0.770 is positive and obtained t <t table is 5.707> 1.990 and the significance value <0.05 is 0,000; 3) there is a positive and significant contribution and leadership style wage system on employee performance proven results Fhitung> Ftable is 62.482> 2.717 and the value of 0.05 is 0,000; 4) the coefficient of determination (R2) obtained 0.607 indicates that the employee's performance is influenced by a combination of leadership styles and wage system amounted to 60.7% comprising 14.4% of leadership style and 46.3% of the wage system and the remaining 39.3% influenced by other variables not examined